Stressful life events and the risk of initial central nervous system demyelination. (June 2017) - Saul, Alice; Ponsonby, Anne-Louise; Lucas, Robyn M; Taylor, Bruce V; Simpson, Steve; Valery, Patricia; Dwyer, Terence; Kilpatrick, Trevor J; Pender, Michael P; van der Mei, Ingrid AF
Background: There is substantial evidence that stress increases multiple sclerosis disease activity, but limited evidence on its association with the onset of multiple sclerosis. Objective: To examine the association between stressful life events and risk of first demyelinating event (FDE). Methods: This was a multicentre incident case–control study. Cases ( n = 282 with first diagnosis of central nervous system (CNS) demyelination, including n = 216 with 'classic FDE') were aged 18–59 years. Controls without CNS demyelination ( n = 558) were matched to cases on age, sex and study region. Stressful life events were assessed using a questionnaire based on the Social Readjustment Rating Scale. Results: Those who suffered from a serious illness in the previous 12 months were more likely to have an FDE (odds ratio (OR) = 2.35 (1.36, 4.06), p = 0.002), and when we limited our reference group to those who had no stressful life events, the magnitude of effect became stronger (OR = 5.41 (1.80, 16.28)). The total stress number and stress load were not convincingly associated with the risk of an FDE. Conclusion: Cases were more likely to report a serious illness in the previous 12 months, which could suggest that a non-specific illness provides an additional strain to an already predisposed immune system.